Automatic assembly design project 1968/9: Report of component supply and separation committee - Gray, A. F.; Hayes, D. A.; Jones, P. V.; Scarr, A. J. (College of Aeronautics, 1969)
This report outlines the techniques for automatically feeding the components of an electrical contact block and describes the design of a feeding system for each component. All components of the contact block were initially analysed for automatic feeding and redesigned where necessary. Existing feeding methods were examined and consideration was given to their versatility. Decisions were then made as to the feeding system for each component.